2011
DOI: 10.1073/pnas.1102017108
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation-induced synchronization in laminar cortical circuits

Abstract: A fundamental feature of information processing in neocortex is the ability of individual neurons to adapt to changes in incoming stimuli. It is increasingly being understood that cortical adaptation is a phenomenon that requires network interactions. The fact that the structure of local networks depends critically on cortical layer raises the possibility that adaptation could induce specific effects in different layers. Here we show that brief exposure (300 ms) to a stimulus of fixed orientation modulates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
73
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 47 publications
11
73
2
Order By: Relevance
“…The effects of adaptation on synchronized IT activity differ from recent reports of an enhancement of synchronization in alpha to gamma frequencies in the supragranular layers in V1 (Hansen and Dragoi 2011) and around 60 Hz in V4 (Wang et al 2011). Stimulus repetition synchronization effects, like attention effects (Chalk et al 2010), may differ between areas, which is possible since synchronization depends on circuit, synaptic, and cellular (e.g., ion channels) properties (Wang 2010).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…The effects of adaptation on synchronized IT activity differ from recent reports of an enhancement of synchronization in alpha to gamma frequencies in the supragranular layers in V1 (Hansen and Dragoi 2011) and around 60 Hz in V4 (Wang et al 2011). Stimulus repetition synchronization effects, like attention effects (Chalk et al 2010), may differ between areas, which is possible since synchronization depends on circuit, synaptic, and cellular (e.g., ion channels) properties (Wang 2010).…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies in early visual cortical areas suggested that coherence can depend on the lamina (Bollimunta et al 2008;Buffalo et al 2011;Hansen and Dragoi 2011;Maier et al 2010) and decreases with interelectrode distance (Hansen and Dragoi 2011;Maier et al 2010;Ray and Maunsell 2011). We have already noted that differences between the two animals in some of the repetition effects diminish when one accepts deeper recordings in monkey K compared with monkey G. Changes in coherence effects with depth may also explain other observed interanimal differences.…”
Section: Effects Of Depth and Distance Between Sites On Lfp-lfp Cohermentioning
confidence: 54%
See 2 more Smart Citations
“…In the somatosensory system, adaptation profoundly shapes the neuronal response along the pathways conveying tactile information to the cortex (Wang et al, 2010;Hansen and Dragoi, 2011). The major mechanism proposed for adaptation in this system is short-term synaptic depression (STD; Tsodyks and Markram, 1997;Chung et al, 2002), in which the response gradually adapts due to the limited synaptic resources and their slow recovery.…”
Section: Introductionmentioning
confidence: 99%